Florística e estrutura espacial: 15 hectares de parcelas permanentes na floresta densa de terra firme na Amazônia central. - SILVA, K. E. da (2010)
Floristic composition and similarity of 15 hectares plots of a terra firme dense forest in Central Amazon, state of Amazonas, Brazil. Estrutura do componente arboreo em 15 ha de parcelas permanentes de floresta densa de terra firme na Amazônia Central. Spatial structure of tree species community in a "terra firme" Amazon forest near Manaus, Brazil. Neighbour's identity of commercial tropical tree species in a tropical rainforest near Manaus, Brazil.